NATIONAL CULTURAL CHARACTERISTICS OF PHRASEMES WITH FOOD/FOOD IN ENGLISH AND UZBEK LANGUAGES - Eshquvvatova Gulasal Abdullo kizi (American Journals, 2023)
The article analyzed the phraseological units representing the concept of food from the point of view of linguoculturalism, to clarify their semantics, to identify, describe and classify the concepts related to people's culture, values, customs, traditions, and social relations, and on this basis to determine the linguistic value of the paremiological units with the concept of food.
Keywords: Phraseological units, food, national mentality, aspirations, culture.